2019
DOI: 10.1080/14686996.2019.1655663
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for ultrahigh outputs generation in triboelectric energy harvesting technologies: from fundamentals to devices

Abstract: Since 2012, a triboelectric nanogenerator (TENG) has provided new possibilities to convert tiny and effective mechanical energies into electrical energies by the physical contact of two objects. Over the past few years, with the advancement of materials' synthesis and device technologies, the TENGs generated a high instantaneous output power of several mW/cm 2 , required to drive various self-powered systems. However, TENGs may suffer from intrinsic and practical limitations such as air breakdown that affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…22,23 In an additional surface treatment of the fabric-based triboelectric energy harvesting device, the PDMScoated fabric was dip-coated using a Fluorinert solution and given a UV/ozone surface treatment to improve the energy harvesting performance of the textile-based triboelectric energy harvesters. 14,15 Figure 1b shows the fabric-based triboelectric energy harvester on clothes, manufactured by the process described in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 In an additional surface treatment of the fabric-based triboelectric energy harvesting device, the PDMScoated fabric was dip-coated using a Fluorinert solution and given a UV/ozone surface treatment to improve the energy harvesting performance of the textile-based triboelectric energy harvesters. 14,15 Figure 1b shows the fabric-based triboelectric energy harvester on clothes, manufactured by the process described in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 This study used unique fabric materials and technology to increase both flexibility of device and energy-generating capability based on UV (Ultraviolet)/ozone surface treatment and Fluorinert-coating. 14,15 Moreover, this study opens up new opportunities for using fabric-based triboelectric energy harvesters as an electrical power sources for next-generation wearable devices.…”
mentioning
confidence: 94%
“…Triboelectric nanogenerator (TENG). The triboelectric effect in 2D materials has recently been reported, with previous devices typically being based on thin films produced through liquid phase exfoliation 15,22,57,58 . Here, we demonstrate the use of mechanically abraded thin films and heterostructures as TENG electrodes.…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…Recently, it has been demonstrated that one strategy for enhancing the power output of a TENG device relies on the use of multilayered structures. In this case, by introducing charge trapping layers such as MoS 2 , the magnitude of induced charge per unit area increases leading to enhanced power output 57,58 .…”
Section: Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…Triboelectric materials are arranged in a triboelectric series based on the electron affinities. Dielectric polymer tribomaterials are showing good usage in the industry for TENG [10]. There are various analytical methods generated theoretically to find the output performance of TENG.…”
Section: Introductionmentioning
confidence: 99%